2004
DOI: 10.1897/03-568
|View full text |Cite
|
Sign up to set email alerts
|

Location‐specific ecotoxicological risk assessment of metal‐polluted soils

Abstract: When chemical analysis indicates metal pollution, a second-tier method is needed to evaluate whether toxic effects occur at the polluted sites. A method based on pollution-induced community tolerance (PICT) was developed using samples taken from locations polluted with sewage more than 20 years ago. Microorganisms extracted from soil samples were exposed to a concentration range of zinc, nickel, copper, chromium (III), or chromium (VI) salts in a buffer suspension. The remaining activity of the intoxicated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…On the other hand, contrary to others studies (He et al 2007;O'Sullivan et al 2013;Rousk et al 2010), our results showed a negative correlation between pH and AOA abundance. Also, there was a negative correlation between AOA and Cr, similar to the results reported previously by Van Beelen et al (2004), who showed that AOA were more affected by contamination from Cu and Cr in a sludgeamended soil, suggesting that AOB have a higher heavy metal tolerance than AOA (Mertens et al 2009). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, contrary to others studies (He et al 2007;O'Sullivan et al 2013;Rousk et al 2010), our results showed a negative correlation between pH and AOA abundance. Also, there was a negative correlation between AOA and Cr, similar to the results reported previously by Van Beelen et al (2004), who showed that AOA were more affected by contamination from Cu and Cr in a sludgeamended soil, suggesting that AOB have a higher heavy metal tolerance than AOA (Mertens et al 2009). …”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have been reported that AOA and AOB are affected by metal pollution, but AOA were more strongly reduced in Cu- (Van Beelen et al 2004;Liu et al 2014), and Zn- (Kelly et al 2011) polluted soils.…”
Section: Discussionmentioning
confidence: 85%
“…Bacteria incubation. Bacteria were extracted from soil immediately before each titration: 15 g of soil sample, based on dry weight, was blended with 150 ml sterile buffer (10 mM bis[2-Hydroxyethyl]iminotris[hydroxymethyl]methane (BisTris, Sigma, http://sigmaaldrich.com) at pH ¼ 7.0) for 1 min at maximum speed and then centrifuged for 10 min at 500 g. According to the method of Van Beelen et al [38], the supernatant was transferred to 2-ml sterile Eppendorf vials, rapidly frozen in liquid nitrogen, and stored at À70 8C until analysis of the community level physiological profiles (CLPP). This final freezing step differs from the original method of Rutgers et al [39], but the CLPP of replicates made at different time points during one year were not significantly different from each other ( p ¼ 0.12), as most fresh suspensions of soil bacteria had very similar BIOLOG profiles and CFU plate counts compared with frozen suspensions [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…The Biolog test has often been used to detect pollution-induced soil community tolerance at sites where sewage sludge has been applied [19]. The present study is based on an agricultural soil historically contaminated with long-term wastewater irrigation.…”
Section: Introductionmentioning
confidence: 99%